Strategy to Improve the Quality of Indonesian Industrial Halal through Smart Investment and Education Systems 4.0 - Gunawan, Ari (KnE Social Sciences, 2020)
Indonesia with a Muslim population reaching 87.17% is very strategic for the development of halal industry. But the halal industry in Indonesia has not grown optimally. One reason is the lack of Islamic financial literacy, whereas literacy greatly influences the financial decisions taken. The government organization, BPJPH, which handles certification and provides Islamic financial literacy, has not yet operated. Therefore we need an innovative solution that is a smart system about Education and Investment for halal industry. The research methodology used is descriptive qualitative. Through quantitative research with one sample t test using descriptive analysis and each 1 research variable. This system is a concept of innovation in the field technology that can be a bridge for government organizations namely BPJPH to provide Islamic financial literacy. Not just giving literacy, but also offering alternative solutions for submission of sharia-compliant capital loans. This system brings together important elements in the halal industry cycle, namely halal industry players, Islamic banking, investors and the government as regulators through an application. Increased Sharia financial literacy and the potential of Return of Investment in halal industries can be realized. This is evidenced by an increase of 80% to the understanding of the halal industry from before, and the potential increase in capital and profits that reached a Return of Investment of 14.3% in the calculation of research samples in the province of East Java. This shows the benefits and success of the application of smart education and investment systems for the halal industry in Indonesia. Keywords: Islamic financial literacy, Islamic finance, technology